A New Type of Statistically Convergent Complex Uncertain Triple Sequence: Birojit Das, Binod Chandra Tripathy, Piyali Debnath - Team, Support (Thai Journal of Mathematics, 2022)
Statistical convergence of complex uncertain triple sequence is already introduced in four aspects of uncertainty. In this article, we initiate the notion of statistical convergence of complex uncertain triple sequence with respect to uniformly almost surely. We prove that statistical convergence with respect to uniformly almost surely of a complex uncertain triple sequence implies its statistical convergence in almost surely. Moreover, we characterized a statistically convergent complex uncertain triple via natural density operator.